Inorganic and natural silicon sources as soil amendment on growth of local aromatic rice variety - Mohd Yusob, Shajarutulwardah; Haruna, Ahmed Osumanu; Omar, Latifah; Kueh, Roland Jui Heng; Kamaruzaman, Rahiniza (Malaysian Society of Plant Physiology, 2023)
Lodging causes a yield loss of approximately 1 ton per hectare as 20% of the total rice production. Silicon(Si) fertilisers significantly improve paddy grain yield, and lodging resistance by improving leaf firmnessbesides promoting better plant canopy and boosting photosynthesis. The objective of this study was todetermine the effects of Si derived from calcium silicate (CaSiO3), rice husk ash, and rice straw on paddyplant growth. A pot study was conducted at MARDI Seberang Perai during the main season (2019/2020)and the off-season (2020) using the MRQ 76 rice variety to evaluate 10 Si carriers. The growth parametersof the paddy plants such as number of tillers, plant height, and chlorophyll content at different growth stageswere evaluated. During season 1, treatment with 100% CaSiO3 (T4) significantly improved the plant height.Nevertheless, the organic Si (T1, T2, and T3) and combination between organic Si with CaSiO3 (T5, T6,T7, and T8) resulted in the tallest plants during season 2. Treatment T7 increased the tillering number permeter square during season 1 whereas in season 2 treatment T8 performed better compared to the standardfertiliser (T9) and control (T10). However, the treatments evaluated in this study did not significantly affectthe chlorophyll content of the paddy plants. Applying a combination of rice straw (50%) and rice husk ash(50%) a day before transplanting, followed by CaSiO3 (100%) as a silicate material during panicle initiation,along with additional NPK fertiliser (17:3:25:2MgO) during heading stage (T7), and without additionalNPK fertiliser (17:3:25:2MgO) at the heading stage (T8) were most effective in enhancing crop growth andmaintaining the paddy cultivation. Therefore, the findings in this study suggested the potential of usinginorganic and organic Si to improve the growth and development of aromatic rice variety.